Substitute \( x = -5 \) into the expression: \[ \frac{(-5)^{2} - 6(-5)}{(-5)^{2} - (-5) - 30} \]
Calculate the numerator: \[ (-5)^{2} - 6(-5) = 25 + 30 = 55 \] Calculate the denominator: \[ (-5)^{2} - (-5) - 30 = 25 + 5 - 30 = 0 \]
The denominator evaluates to \( 0 \), which means the expression is undefined at \( x = -5 \). Therefore, the limit does not exist (DNE).
\(\boxed{\text{DNE}}\)
Oops, Image-based questions are not yet availableUse Solvely.ai for full features.
Failed. You've reached the daily limit for free usage.Please come back tomorrow or visit Solvely.ai for additional homework help.